Ordered RTiO2@ATiO2 architecture for dye-sensitized solar cell applications. Issue 108 (8th November 2016) - Liu, Y. L.; Wang, D. D.; Ni, J.; Zhang, S. F.; Jin, X. J.; Lv, S. J.; Wang, Z. W.; Lei, J. F.
Abstract : RTiO2 @ATiO2 architectures are constructed, in which 1D rutile TiO2 (RTiO2 ) arrays allow a fast electron transport and branched anatase TiO2 (ATiO2 ) particles benefit the dye harvesting. Abstract : Herein, we report a green and convenient method to prepare a compact layer for better construction of hierarchical TiO2 architectures to serve as photoanodes, in which one-dimensional (1D) rutile TiO2 (RTiO2 ) arrays are grown hydrothermally on a compact layer for fast electron transport, and branched anatase TiO2 (ATiO2 ) particles are deposited orderly on RTiO2 backbones for high efficiency dye harvesting. Characteristic tests indicate that the 1D RTiO2 arrays are tetragonal in shape with a square top surface, whereas the branched ATiO2 particles are nanoconic in shape with exposed {001} facets. As a result, the RTiO2 @ATiO2 photoanode, sensitized by the N719 dye, harvests a solar energy conversion efficiency of 5.68%, which is nearly 3 times higher than that found in the RTiO2 array-based dye-sensitized solar cell (DSSC), which demonstrates that the RTiO2 nanorods decorated by ATiO2 nanocones are helpful in enhancing the solar energy conversion efficiency.